Laparoscopy in endometriosis - Rechkemmer Prieto, Adolfo (2015)
Endometriosis surgical treatment is directed to pain relief and recovery of reproductive function by removal of implants and reconstruction of pelvic anatomy alterations. Compared with laparotomy, laparoscopic treatment of endometriosis allows shorter time of hospitalization, faster recovery, smaller incisions, more accessibility and magnification of deep recto-vaginal nodules. Laparoscopic ablation of both endometriotic implants and uterosacral nerves (LUNA) in minimal to moderate disease reduces endometriosis-associated pain compared with diagnostic laparoscopy alone. In infertility associated to endometriosis ablation of endometriotic implants and adhesiolysis improve fertility in minimal and mild endometriosis, compared with diagnostic laparoscopy. In cases of 4 cm or larger endometriomas, laparoscopic cystectomy improves fertility compared with drainage and cauterization. Laparoscopic cystectomy must be carefully performed to avoid damage of normal ovarian tissue in order to preserve ovarian reserve. It is important to refer patients with severe endometriosis and bowel or ureter involvement or recto-vaginal septum deep nodules to higher complexity centers, where more well equipped experienced surgeons will be able to perform complex laparoscopic surgery.